2013
DOI: 10.1128/jvi.01210-13
|View full text |Cite
|
Sign up to set email alerts
|

The Measles Virus Hemagglutinin β-Propeller Head β4-β5 Hydrophobic Groove Governs Functional Interactions with Nectin-4 and CD46 but Not Those with the Signaling Lymphocytic Activation Molecule

Abstract: Measles virus (MV), which belongs to the family Paramyxoviridae within the order Mononegavirales (1), may be the most contagious aerosol-transmitted virus circulating in human populations (2). In 2010, about 139,000 people died from secondary infections due to MV-induced immune suppression (3, 4). While a worldwide vaccination campaign aiming at eradication is ongoing (5), diminishing vaccine coverage in the United States and Europe has caused a rebound of measles cases in 2011, threatening the feasibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 52 publications
4
35
0
Order By: Relevance
“…All four paramyxoviruses considered here enter cells by fusion at the plasma membrane at a neutral pH; however, the attachment proteins of respiroviruses and rubulaviruses bind ubiquitous sialic acids, while the attachment proteins of morbilliviruses bind the receptors SLAM and nectin-4 (18). Tissue-specific expression of SLAM and nectin-4 appears to be a main determinant of MV tropism (18,19), and the biological properties of these receptors may also facilitate steps of the pathogenic process.…”
mentioning
confidence: 97%
“…All four paramyxoviruses considered here enter cells by fusion at the plasma membrane at a neutral pH; however, the attachment proteins of respiroviruses and rubulaviruses bind ubiquitous sialic acids, while the attachment proteins of morbilliviruses bind the receptors SLAM and nectin-4 (18). Tissue-specific expression of SLAM and nectin-4 appears to be a main determinant of MV tropism (18,19), and the biological properties of these receptors may also facilitate steps of the pathogenic process.…”
mentioning
confidence: 97%
“…Since receptor engagement promotes F's fusion activity, constant receptor engagement may permit an HN/F pair to resist inhibition by fusion-inhibitory peptides (60). Interaction of measles virus H with its receptor is dynamic, with on and off events between individual molecules (61), while the affinity of the overall complex is maintained (27,62). We hypothesized that reducing the number of MV H attachment proteins interacting with CD150 receptor molecules would increase the fusion inhibition efficacy of peptides.…”
Section: Hpiv3 F-derived Hrc Peptides Inhibit Wt MV Entrymentioning
confidence: 99%
“…Recent structural studies revealed that all three receptors of MV bind close to a hydrophobic groove located between blades 4 and 5 (␤4-␤5 groove) of the measles H protein ␤-propeller head (32-34). Mateo et al recently reported that there is a strong overlap between the functional footprints of nectin4 and CD46 but not SLAM (35). Based on these studies, it is thus not surprising that ablation of nectin4 binding in VSVFH would result in a significant compromise in H usage of CD46 and impairment of its oncolysis of human cancer cells.…”
Section: Discussionmentioning
confidence: 98%